2020
DOI: 10.1021/acscatal.0c01284
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doped Mn3O4 Spinel Nanoparticles with Highly Exposed Feoct–O–Mntet Sites for Efficient Selective Catalytic Reduction (SCR) of NO with Ammonia at Low Temperatures

Abstract: The development of highly active catalysts for ammonia selective catalytic reduction (NH 3 -SCR) of NO at low temperatures and the exploration of efficient catalytic active sites are desirable but still challenging. Herein, a series of Fe x Mn 3−x O 4 nanoparticles (NPs) were synthesized, derived from Mn−Fe bimetallic MOFs. The Fe 0.35 Mn 2.65 O 4 NPs exhibit a NO conversion up to 90% at 180 °C in an ultrahigh GHSV of 400 000 h −1 . An efficient Fe oct −O−Mn tet site is revealed, and the formation energy of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…To further identify the behavior of surface sulfates, XPS spectra of O 1 s shown in Figure C revealed that there were two sub-bands for the as-prepared catalysts. The first one around 530.0 eV belonged to lattice oxygen species (O β ), and the second one around 532.0 eV was assigned to surface-absorbed oxygen species (O α ), which could originate from surface sulfate . The ratio of O α /(O α + O β ) for Fe-S/Ti-H increased from 33 to 45% after K poisoning, while the ratio for Fe-S/Ti-L was almost identical to that for K-Fe-S/Ti-L, which was consistent with the results of Raman and XPS S 2p.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…To further identify the behavior of surface sulfates, XPS spectra of O 1 s shown in Figure C revealed that there were two sub-bands for the as-prepared catalysts. The first one around 530.0 eV belonged to lattice oxygen species (O β ), and the second one around 532.0 eV was assigned to surface-absorbed oxygen species (O α ), which could originate from surface sulfate . The ratio of O α /(O α + O β ) for Fe-S/Ti-H increased from 33 to 45% after K poisoning, while the ratio for Fe-S/Ti-L was almost identical to that for K-Fe-S/Ti-L, which was consistent with the results of Raman and XPS S 2p.…”
Section: Resultssupporting
confidence: 83%
“…The first one around 530.0 eV belonged to lattice oxygen species (O β ), and the second one around 532.0 eV was assigned to surfaceabsorbed oxygen species (O α ), which could originate from surface sulfate. 38 The ratio of O α /(O α + O β ) for Fe-S/Ti-H increased from 33 to 45% after K poisoning, while the ratio for Fe-S/Ti-L was almost identical to that for K-Fe-S/Ti-L, which was consistent with the results of Raman and XPS S 2p. The overall atomic ratio of each element obtained from XPS survey results further confirmed the deduction that sulfate would migrate from the bulk phase to surface to protect the active iron species from K poisoning (Table S1).…”
Section: No Conversion (%)supporting
confidence: 84%
“…The introduction of Ce can further significantly improve the deNO x activity at low-temperatures, and its NO x conversion can reach 95% at 100 °C. As our previous reports [10][11][12], the NH 3 -SCR reaction (4NH 3 + 4NO + O 2 → 4N 2 + 6H 2 O) at lowtemperatures can be considered as the coupling of NO oxidation (2NO + O 2 → 2NO 2 ) and "Fast SCR" reaction (2NH 3 + NO + NO 2 → 2N 2 + 3H 2 O), where the "Fast SCR" reaction can occur rapidly. Therefore, the NO oxidation activity of catalyst could determine its NH 3 -SCR activity.…”
Section: Catalytic Activity Testmentioning
confidence: 83%
“…[11][12][13][14] The intrinsic activity of the catalyst also has an important effect on the removal of soot and NO x . 15,16 It should be noted that there is a "trade-off" relationship between the removal of soot and that of NO x in diesel exhaust emissions, thus it is difficult to research and develop a highly active catalyst for the simultaneous removal of soot and NO x . Therefore, a combination of two specific properties of efficient catalysts was used to design a novel catalyst.…”
Section: Introductionmentioning
confidence: 99%